2003
DOI: 10.1063/1.1622986
|View full text |Cite
|
Sign up to set email alerts
|

Spin blockade in ferromagnetic nanocontacts

Abstract: Using a free-electron model and a linear response theory we investigate spin-dependent electronic transport in magnetic nanocontacts in the ballistic regime of conduction. We emphasize the fact that in atomic-size ferromagnetic contacts it is possible to achieve the conductance value of e2/h, which implies a fully spin-polarized electric current. We explore some consequences of this phenomenon. In particular, we show that the presence of a nonmagnetic region in the nanocontact separating two ferromagnetic elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…[101]. This observation is in accordance with a calculation finding fully lifted spin degeneracy for ferromagnetic ballistic contacts [102].…”
Section: Magnetism Of Individual Surface Adsorbed Atoms Probed By Stmsupporting
confidence: 80%
“…[101]. This observation is in accordance with a calculation finding fully lifted spin degeneracy for ferromagnetic ballistic contacts [102].…”
Section: Magnetism Of Individual Surface Adsorbed Atoms Probed By Stmsupporting
confidence: 80%
“…In contrast, a series of recent experiments on magnetic nanostructures, and particularly nanowires, revealed that the magnetoresistance in the presence of DWs can be as large as several hundreds [4,5] or even thousands [6,7] of percents. These observations have decisive consequences in so far as DWs are controllable efficiently by applying a magnetic field [8] and can also be steered by a spin-polarized electric current [9], meaning that the magnetoresistance of the structure containing DW is controllable via an electric field.The interpretation of the huge magnetoresistance of DWs observed in magnetic semiconductor (in the ballistic quantum regime) relies on the relative sharpness of DWs on the scale set by the wavelength of carriers (electrons or holes) [10,11,12,13,14]. In such a situation spin-dependent scattering of carriers from DWs is greatly enhanced.…”
mentioning
confidence: 99%
“…The interpretation of the huge magnetoresistance of DWs observed in magnetic semiconductor (in the ballistic quantum regime) relies on the relative sharpness of DWs on the scale set by the wavelength of carriers (electrons or holes) [10,11,12,13,14]. In such a situation spin-dependent scattering of carriers from DWs is greatly enhanced.…”
mentioning
confidence: 99%
“…Our consideration is valid for complex wave vectors (17) which allows for extending this method to systems with insulating layers. Also our consideration can be applied to systems with fi nite lateral dimensions like magnetic nanowires [12].…”
Section: Resultsmentioning
confidence: 99%